The Art and Science of Effective Time Management - Shrivastava, Umesh Prasad (International Journal of Social Sciences and Management, 2014)
No abstract DOI: http://dx.doi.org/10.3126/ijssm.v1i2.10105 Int. J. Soc. Sci. Manage. Vol-1, issue-2: 58-59